Integrating the PV-Diesel Hybrid System for Reliability Improvement in Distribution System - Cho Cho Myint; Ohn Zin Lin; Soe Soe Ei Aung (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
In Myanmar, as the main power generation is hydro power generation. the utility cannot supply sufficient power to customers during the dry season. Besides interruptions occur frequently due to aging system and lack of prospered protection. Therefore, reliability is an urgent issue in Myanmar. As a result of unbalance between generation and load, the distribution system is getting poor voltage profile, instability and high power losses in high load condition. According to network characteristics, the failure of a component always leads to consequence interruption in a radial distribution system.  Therefore, it is a must consideration to mitigate these challenges to enhance the system reliability. There are many techniques to solve the reliability problems such as reclosers, switching devices (manual and automated switches), system reconfiguration, feeder re-conducting and integration of distributed generation (DG). In this paper, system reliability assessment is evaluated in detail with the integration of the distributed generation such as PV-Diesel Hybrid System. The location of DG is chosen according to the expected energy not supply (EENS) and the voltage drop in proposed system. Next, the optimal sizing of DG is chosen depends on the penetration level of generator. Reliability indices can be evaluated depending on the failure rate(λ), repair time(r) and annual outage time(U) in Electrical Transient and Analysis Program (ETAP) software. The case study of this thesis is carried out in 33/11 kV network which is connected Kyatminton Substation, Kyaukse, Middle Myanmar.Keywords: distributed generation, distribution system, EENS, reliability, reliability indices.